Ciprofloxacin Treatment of Bacterial Peritonitis Associated with Chronic Ambulatory Peritoneal Dialysis Caused by Neisseria cinerea - Taegtmeyer, M. (American Society for Microbiology, 2006)
Bacterial peritonitis is a well-recognized complication of chronic ambulatory peritoneal dialysis (CAPD) in patients with end-stage renal failure. We present a case of peritonitis due to an unusual pathogen, Neisseria cinerea, unresponsive to the standard intraperitoneal (i.p.) vancomycin and gentamicin, which responded rapidly to oral ciprofloxacin.